Safety and Immunogenicity of ALVAC vCP1452 and Recombinant gp160 in Newly Human Immunodeficiency Virus Type 1-Infected Patients Treated with Prolonged Highly Active Antiretroviral Therapy - Jin, Xia (American Society for Microbiology, 2002)
In order to boost immune responses in persons in whom highly active antiretroviral therapy (HAART) was initiated within 120 days of the onset of symptoms of newly acquired human immunodeficiency virus type 1 (HIV-1) infection, we administered vaccines containing a canarypox virus vector, vCP1452, with HIV-1 genes encoding multiple HIV-1 proteins, and recombinant gp160. Fifteen HIV-1-infected subjects who achieved sustained suppression of plasma viremia for at least 2 years were enrolled. While continuing antiretroviral therapy, each subject received at least four intramuscular injections of the vaccines on days 0, 30, 90, and 180. Adverse events were mild, with the most common being transient tenderness at the vCP1452 injection site. Of the 14 patients who completed vaccination, 13 had significant increases in anti-gp120 or anti-p24 antibody titers, and 9 had transient augmentation of their T-cell proliferation responses to gp160 and/or p24. HIV-1-specific CD8(+) T cells were quantified using an intracellular gamma interferon staining assay. Among 11 patients who had increased CD8(+) T-cell responses, seven had responses to more than one HIV-1 antigen. In summary, vaccination with vCP1452 and recombinant gp160 appears safe and immunogenic in newly HIV-1-infected patients on HAART.